Simulasi Deteksi Posisi dan Lintasan Roket Menggunakan Algoritma TDOA-Trilateration pada Sistem Radar Sekunder - Achmad, Shulchul Chabib; Darjat, Darjat; Christyono, Yuli; Ngatelan, Ngatelan (Departemen Teknik Elektro, Universitas Diponegoro, 2011)
Position and trajectory detection of rockets is very nessesary for the lauch of rockets can work as expected. If position and trajectory of rockets aren’t monitored properly, it could be bad. Therefore, we need solutions to monitor the position and trajectory rockets with the technical studies in particular. Rockets moves with initial power and power when rockets fly until its produce acceleration. The rockets movement are arranged by the law of mechanics orbital and its are affected by the law of aerodynamics. The output result from this detection, will be used as comparative data with the expected trajectory. Through this final project, we simulate application of TDOA-Trilateration Algorithm for detect position and trajectory of rocket on secondary radar system. Technique for get distance between transceiver station and transponder is with find time difference of transmit and receive signal between transceiver station and transponder. This technique is called with TDOA (Time Difference Of Arrival). After Distance between transceiver station and transponder is known, three-dimensional position can be searched with Trilateration methode. This prosses will be simulated with software Matlab R2008a. On the simulation testing indicate that rockets position and trajectory which result from simulation of rockets trajectory formation stage with simulation stage to detect position and trajectory of rockets have the same x, y, z values. However, there is one point of positioan which haven’t the same z value while the z value is negatif. Variation values of D0, D1, and D2 (the placement of Ground Station) aren’t influential to the detection values (x, y,z), but influential to values of deltaT1, deltaT2, and deltaT3. Keyword : TDOA (Time Difference Of Arrival), Trilateration, rockets, transceiver, transponder.